Analisis Strategi Pengembangan Bisnis Dengan Pendekatan Business Model Canvas (BMC) Dalam Upaya Mencapai Keunggulan Bersaing - Misdaniawan Misdaniawan; Hadi Purwanto (JURUTERA - Jurnal Umum Teknik Terapan, 2017)
Keju Kesu competition that demands professional management performance and full knowledge of its business in order to evaluate and determine competitive strategies. This newly established 1 year company needs to develop a better business strategy. This research is meant to know a new design of business model as a business development strategy in Keju Kesu with business model canvas approach. Using qualitative method by doing interview, while questionnaire is used to formulate the strategy, then using businedd model canvas to analyze which every building block is also being analyzed by Matrix IFE & EFE, Matrix IE, Matrix SWOT, and blue ocean strategy that is combined with business model canvas. Research's result indicates that recent business model of Keju Kesu is Hold and Mantain-stage reviewed from ascpects of business model canvas which analyzed by Matrix IFE and Matrix EFE that produced Matrix IE at Keju Kesu on kuadran V, proper alternative strategy to be used on this kuadran is market penetration strategy and product development. Matrix SWOT and blue ocean strategy analysis results are that Jaya Bakery has to read the market progress more and place the product by maximizing media, internet, social media. Adding value to a product, creating a continuous relation with customer, action key is to involve technology, placing and upgrading competen human resources and product inovation that maintain low price.